A socialização de professores na formação básica: relações entre modos de constituição de grupos e manifestações de graduandos sobre a função docente - Silva, Luizana Rocha Migueis Ferreira da (2007)
This research aims to describe and analyze the teachers process of socialization in their basic formation in the Pedagogy course. We specifically analyzed ways of group formation among the subjects and relations to manifestation of ideas on the teaching function. The research had an empirical nature and contemplated the use of sociometric test, questionnaire and projective questions. We intended to show, by means of the action in the group and by the possibility of interaction among the subjects in the groups, that the subjects demonstrate fragments of the teaching habitus in formation in the graduation. The research had as main theoretical referential Pierre Bourdieu s studies, besides important works by Gimeno Sacristán, Viñao Frago, Jacob Levy Moreno, Georges Bastin and Norbert Elias. The key concepts used in the research in order to understand the process of socialization were Bourdieu s concepts of field and habitus. The main aspects identified and related to the constitution of groups among the subjects were the teaching practice or non-practice, the teaching course in Secondary School level and the academic performance. The teaching practical dimension was presented as an important element in the definition of the groups and in the manifestations on the teaching function. The choices carried through for academic or professional works are keys to understand how the groupings in the teachers formation in the graduation are constituted. That way, it was confirmed the idea of relevance of the study about the groups and their ways of constitution for the understanding of the future teachers socialization